(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes in detail the importance and advantages of the state curriculum "First Step" in increasing the monitoring of the preparation group of the children of the preparatory group of the preschool education organization.